2016
DOI: 10.1111/hsc.12385
|View full text |Cite
|
Sign up to set email alerts
|

Rural residents' perspectives on the rural ‘good death’: a scoping review

Abstract: The 'good death' is one objective of palliative care, with many 'good death' viewpoints and research findings reflecting the urban voice. Rural areas are distinct and need special consideration. This scoping review identified and charted current research knowledge on the 'good' rural death through the perspectives of rural residents, including rural patients with a life-limiting illness, to identify evidence and gaps in the literature for future studies. A comprehensive literature search of English language ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…There were both good and bad experiences, good moments and terrible narratives of the poor communication that left a negative imprint on the family member’s EOL experience and grieving process. In terms of what components made up the good death experience, the results closely align with previous scholarship in the good death literature, including pain and symptom management, clear decision-making, preparation for death and communication [6,7,12,14,17,57,58]. Furthermore, the results align with an earlier meta-synthesis of EOL care from the family perspective that reported the necessity of quality communication among healthcare participants and clinicians being open about imminent death [30].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…There were both good and bad experiences, good moments and terrible narratives of the poor communication that left a negative imprint on the family member’s EOL experience and grieving process. In terms of what components made up the good death experience, the results closely align with previous scholarship in the good death literature, including pain and symptom management, clear decision-making, preparation for death and communication [6,7,12,14,17,57,58]. Furthermore, the results align with an earlier meta-synthesis of EOL care from the family perspective that reported the necessity of quality communication among healthcare participants and clinicians being open about imminent death [30].…”
Section: Discussionsupporting
confidence: 77%
“…The results illustrate consensus on certain ideas such as the importance of pain management, but there were also differences that indicate a highly individualized definition of a good death that included socio-cultural factors that defined quality of life [13,17]. Both reviews concluded with a call for more research [13,17]. More, specifically there was a call for healthcare participants at end of life to engage in more open, public dialogue surrounding death and dying [13].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the Southern region, Tennessee is surpassed only by Kentucky, West Virginia, and Arkansas on both measures for lack of hospice facilities [13]. Despite the fact that the majority of individuals have expressed a desire to die at home and rural individuals expressed a desire for a peaceful death without suffering, hospice enrollment remains low: approximately 6% for adult PLWHA and <1% for pediatric and adolescent patients with AIDS [23][24][25][26]. End-of-life services, like hospice, are likely inaccessible within Appalachian regions due to known barriers of rural geographic landscape, remote access of the region and marginalization [9,10].…”
Section: Plos Onementioning
confidence: 99%